Peran Mata Kuliah Manajemen Sumber Daya Manusia dalam Meningkatkan Kompetensi Mahasiswa - Alfi Nura; Tasya Maulita; Angel A Sihombing; Khaila Aininda Saragih; Sabar Saur Matua; Ilsa Mariska Nasution; Yosheline Belvri Saragih (Universitas Negeri Medan, 2026)
This study aims to analyze the role of the Human Resource Management (HRM) course in developing and improving students’ competencies as qualified human resources. This research uses a descriptive qualitative approach with students of the Office Administration Education Study Program, Faculty of Economics, Universitas Negeri Medan as the subjects. Data were collected through observation, interviews, and documentation, and analyzed using an inductive approach.The results show that the HRM course plays an important role in enhancing students’ competencies, including knowledge, skills, attitudes, and social abilities. Competency development is carried out through active learning methods such as discussions, presentations, assignments, and case studies. These learning activities improve critical thinking, communication, teamwork, and foster professional attitudes among students. In conclusion, the HRM course contributes to shaping competent, high-quality students who are ready to face the demands of the workplace. Therefore, HRM learning should continue to be developed to remain relevant to industry needs.